The Coronal Pulp Cavity Index an aid in age determination -A Cone Beam Computed Tomography Study - Ceena Denny E1 , Bastian TS2 , Srikant Natarajan3 , Nithin Thilak4 , Almas Binnal5 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The objective of the present study was to assess the accuracy of age estimation from TCI ofmandibular molars (except wisdom teeth) of both sides using CBCT images of known age and sex, so thatwe can apply this method to estimate age in both living individuals and skeletal material of unknown age.Methods: A cross sectional retrospective study was conducted on a total of 100 CBCT images of subjectswho were referred to the department for varied diagnostic purposes of known age and gender. All CBCTimages with a fully visible pulp cavity were selected. Two measurements were taken at two different levels.Height of the crown (CH) and height of the coronal pulp cavity (CPCH). Then tooth – coronal index (TCI)for each tooth was calculated as follows: TCI = CPCH X 100 / CH.Results: Comparison of TCI value between male and female showed no significant difference between thegender. Among the four mandibular molars (lower left and right1stand 2nd molars) 46 and 47 TCI correlateswell with age. TCI of 46 has significant prediction of age in female with an R value of 0.426. Inter observermeasurements showed a moderate to good agreement of the measures.Conclusions: TCI method of mandibular teeth was found to be a reliable method for age estimation and notgender determination. CBCT can be used in age determination for forensic purposes as it is non- invasiveand also makes it possible to reconstruct the images in different planes showing the anatomical and imagedstructures at different planes.